1999
DOI: 10.1109/50.803024
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a double-pass backward Er-doped superfluorescent fiber source for fiber-optic gyroscope applications

Abstract: The characteristics including mean wavelength stability, linewidth, and output power of a double-pass backward (DPB) Er-doped superfluorescent fiber source (SFS) are theoretically analyzed in details. The effects of the variations in fiber length, pump wavelength, fiber mirror reflectance, optical feedback, and erbium concentration on the characteristics are investigated. The analysis results show that an SFS in DPB configuration may serve as light source for the navigation-grade fiber-optic gyroscope applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…28 Our devices are electrically resistive in their asdeposited state, with no evidence of metallic filament formation. If metal filaments are responsible for the switching and memory effects in our devices, then these must result from the formation process.…”
Section: -8mentioning
confidence: 97%
“…28 Our devices are electrically resistive in their asdeposited state, with no evidence of metallic filament formation. If metal filaments are responsible for the switching and memory effects in our devices, then these must result from the formation process.…”
Section: -8mentioning
confidence: 97%
“…An analysis of the current-voltage curves of the PMMA:BCP:TCNQ [1:1:0.5 wt%] CT complex device [ Figure 5] suggested that the transition from the highresistance to the low-resistance state took place due to the charge transfer mechanism [29][30][31]. The linear fitting of Ln(I) versus V 1/2 in the OFF state [ Figure 5(a)] and of log I versus log V in the ON state [best fitting of log I-log V are I ∝ V 1.56 during the first bias scan and I ∝ V 1.24 in the third bias scan, Figure 5(b)] indicate that the current (charge transport) was controlled by the direct charge injection from Al to the CT complex (thermionic emission model [35,36]) in the OFF state and by the space-chargelimited current (SCLC) in the ON state [35,37], and not by filament conduction, which results in metallic behavior [14,15] (log I-log V is I ∝ V…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the device did not show current or V th dependence with a change of the active area in the pixel. These results strongly suggest that the conductivity change can be realized by the filament, as formed by defects or dust on the bottom of the substrate [15]. More experiments, such as the current and V th variations according to the film thickness of the CT complex, the temperature, and the timedependence of the conductivity of the device should be carried out to determine the switching mechanism of CT complex devices.…”
Section: 0mentioning
confidence: 99%
See 2 more Smart Citations